“A Cadential Sense of Rhythm”: Dennis Lee on Poetics and Music - Leckie, Ross (Studies in Canadian Literature, 2001)
The interview focuses on poetry and jazz, and Lee's use of rhythm and meter. There is a discussion of many other poets including, Wallace Stevens, John Ashbery, Al Moritz, Marlene Cookshaw, Don McKay, Fred Wah, Paul Celan and Philip Lamantia. Lee discusses the books he is reading, as well as his current projects.